Suppression of the inflammatory response by diphenyleneiodonium after transient focal cerebral ischemia - Nagel, Simon; Pfleger, Karin; Grond-Ginsbach, Caspar; Wagner, Simone (Journal of neurochemistry, 2012)
Diphenyleneiodonium (DPI), a NADPH oxidase inhibitor, reduces production of reactive oxygen species (ROS) and confers neuroprotection to focal cerebral ischemia. Our objective was to investigate whether the neuroprotective action of DPI extends to averting the immune response. DPI-induced gene changes were analyzed by microarray analysis from rat brains subjected to 90 min of middle cerebral artery occlusion, treated with NaCl (ischemia), dimethylsulfoxide (DMSO), or DMSO and DPI (DPI), and reperfused for 48 h. The genomic expression profile was compared between groups using ingenuity pathway analysis at the pathway and network level. DPI selectively up-regulated 23 genes and down-regulated 75 genes more than twofold compared with both DMSO and ischemia. It significantly suppressed inducible nitric oxide synthase signaling and increased the expression of methionine adenosyltransferasesynthetase 2A and adenosylmethionine decarboxylase 1 genes, which are involved in increasing the production of the antioxidant glutathione. The most significantly affected gene network comprised genes implicated in the inflammatory response with an expression change indicating an overall suppression. Both integrin- and interleukin-17A-signaling pathways were also significantly associated and suppressed. In conclusion, the neuroprotective effects of DPI are mediated not only by suppressing ischemia-triggered oxidative stress but also by limiting leukocyte migration and infiltration.
Gesehen am 04.09.2018